ORGANIZATION PRACTICES OF THE DEAF COMMUNITY: ARTICULATIONS FROM CULTURE - Liane Camatti; Márcia Lise Lunardi-Lazzarin (Editora da Universidade de Santa Cruz do Sul, 2015)
The deaf community has often been understood as a safe place in which the deaf difference can be reliably and cozily experienced. The aim of this paper is to understand how the deaf community is organized and narrated as such. Post-structuralist studies have been used to analyze the materials produced for this research. Deaf teachers and students from deaf schools who have actively participated in community movements were interviewed. The analysis of the materials has shown that belonging to a community involves following a living code created with a common intention. In the deaf community, the reference grounding its organization is what has been known as cultural artifacts of deaf people. However, belonging to the community is delimited by the extent to which one is able or willing to move in accordance to the community rules. Thus, we can see that the community aggregates elements other than just the feeling of being deaf, only justified by sharing the same culture.